Participant experiences in the Diabetes REmission Clinical Trial (DiRECT). Issue 1 (18th September 2021) - Rehackova, Lucia; Rodrigues, Angela Margarete; Thom, George; Brosnahan, Naomi; Barnes, Alison C.; McCombie, Louise; Leslie, Wilma S.; Zhyzhneuskaya, Sviatlana; Peters, Carl; Adamson, Ashley J.; Lean, Michael E.J.; Taylor, Roy; et al.
Abstract: Introduction: The Diabetes REmission Clinical Trial (DiRECT) has shown that sustained remission of type 2 diabetes in primary care is achievable through weight loss using total diet replacement (TDR) with continued behavioural support. Understanding participants' experiences can help optimise the intervention, support implementation into healthcare, and understand the process of behaviour change. Methods: Thirty‐four DiRECT participants were recruited into this embedded qualitative evaluation study. In‐person and telephone interviews were conducted before the TDR; at week 6–8 of the TDR; 2 weeks into food reintroduction (FR); and at 1 year, to learn about participant experiences with the programme. Transcribed narratives were analysed thematically, and we used interpretation to develop overarching themes. Results: Initiation of the TDR and transition to FR were challenging and required increased behavioural support. In general, adhering to TDR proved easier than the participants had anticipated. Some participants chose the optional extension of TDR. Rapid weight loss and changes in diabetes markers provided ongoing motivation. Further weight loss, behavioural support and occasional use of TDR facilitated weight loss maintenance (WLM). A process of behaviour adaptation to change following regime disruption was identified in three stages: (1) expectations of the new, (2) overcoming difficulties with adherence, and (3) acceptance of continuous effort and establishment of routines. Conclusions: The DiRECT intervention was acceptable and regularity, continuity, and tailoring of behavioural support was instrumental in its implementation in primary care. The adaptation process accounts for some of the individual variability of experiences with the intervention and highlights the need for programme flexibility.